2012
DOI: 10.1016/j.ydbio.2012.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Median facial clefts in Xenopus laevis: Roles of retinoic acid signaling and homeobox genes

Abstract: The upper lip and primary palate form an essential separation between the brain, nasal structures and the oral cavity. Surprisingly little is known about the development of these structures, despite the fact that abnormalities can result in various forms of orofacial clefts. We have uncovered that retinoic acid is a critical regulator of upper lip and primary palate development in Xenopus laevis. Retinoic acid synthesis enzyme, RALDH2, and retinoic acid receptor gamma (RARγ) are expressed in complementary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 69 publications
4
66
0
Order By: Relevance
“…Thus, the upregulation of Lhx8 by enhanced FGF signaling and its down-regulation by blocking of the FGF receptor, indicate that Lhx8 transcription is controlled by FGF signaling during growth of the maxillary prominence. It has been suggested that RA signaling regulates Msx2 and Lhx8 expressions directly or indirectly by activating intermediate pathway such as FGF (14). Our findings confirm that Lhx8 expression is primarily controlled by the FGF signaling pathway and depends on local RA concentration.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, the upregulation of Lhx8 by enhanced FGF signaling and its down-regulation by blocking of the FGF receptor, indicate that Lhx8 transcription is controlled by FGF signaling during growth of the maxillary prominence. It has been suggested that RA signaling regulates Msx2 and Lhx8 expressions directly or indirectly by activating intermediate pathway such as FGF (14). Our findings confirm that Lhx8 expression is primarily controlled by the FGF signaling pathway and depends on local RA concentration.…”
Section: Discussionsupporting
confidence: 86%
“…Insufficient levels of RA may induce the downregulation of those genes lead to specific defects on the maxilla because Msx gene products have a role on mediating the effect of RA on facial development (19). A study in Xenopus embryo suggests a model whereby RA signaling regulates Lhx8 and Msx2, which together direct the upper lip and palate morphogenesis (14). RA homeostasis appears to be vital for normal Lhx8 expression as both addition and inhibition of RA leads to aberrant expression of Lhx8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Loss of function of lhx8 (together with msx2) in frogs resulted in a median cleft in the upper lip and primary palate; both genes were suggested to be regulated by retinoic acid signalling. 11 Thus, animal studies indicate that the gene has a role in orofacial development and is a very good candidate for the trait observed in the presented family. Additional research could help determine whether or not the 273-kb deletion sequences contain any elements that regulate LHX8.…”
Section: Discussionmentioning
confidence: 77%
“…Xenopus laevis is an ideal model for study of craniofacial development as embryos are large, develop externally, and the face is readily visible, allowing micromanipulation and imaging of development. Mechanisms underlying facial development appear conserved, indicating that findings made in the frog provide insight into human development 4,[15][16] .…”
Section: Introductionmentioning
confidence: 99%